Choosing factors : the international evidence - Grobys, Klaus; Kolari, James W. (Routledge, Taylor & Francis Group, 2021)
Extending Fama and French’s U.S. study on choosing factors to international equity markets, we test nested and non-nested asset pricing models for North America, Europe, Asia excluding Japan, and Japan. For non-nested models, we propose a new simulation methodology using a blocks bootstrap approach that takes into account factor dependencies. The resultant out-of-sample Sharpe ratios across all models and countries are lower than Fama and French’s pairs bootstrap approach. While we confirm that the six-factor model with market, size, and small size spread factors for value, profitability, investment, and momentum produces the highest maximum squared Sharpe ratio in most economies, an exception is Asia excluding Japan. Additionally, spanning regressions reveal that size does not matter in any of the international equity markets, whereas value matters in Europe, Asia excluding Japan, and Japan.
Keywords: Risk factors; maximum squared sharpe ratio; asset pricing models; spanning regressions; international equity markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|